2020
DOI: 10.3389/fcvm.2020.00136
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS-5 Decreases in Aortas and Plasma From Aortic Dissection Patients and Alleviates Angiotensin II-Induced Smooth Muscle-Cell Apoptosis

Abstract: Background: Acute aortic dissection (AAD) is associated with degeneration of the aortic media and accompanied by vascular extracellular matrix (ECM) remodeling. Recently, a disintegrin and metalloproteinase with thrombospondin type 1 motifs-5 (ADAMTS-5) has been reported to be involved in ECM remodeling and vascular diseases. The aim of this study was to examine ADAMTS-5 levels in AAD patients and investigate the underlying mechanisms. Methods: Aortic tissue samples were collected from normal donors and AAD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In studies of TAAD, the mRNA levels of ADAMTS-5 are found to be decreased [30,161] and this has been recently confirmed at the protein level, both in plasma and in aortic biopsies [152]. Mouse models of TAAD may help to clarify the role of ADAMTS-5 in this disease.…”
Section: Proteoglycans and Proteoglycanases In Cardiovascular Physiology And Diseasementioning
confidence: 94%
See 1 more Smart Citation
“…In studies of TAAD, the mRNA levels of ADAMTS-5 are found to be decreased [30,161] and this has been recently confirmed at the protein level, both in plasma and in aortic biopsies [152]. Mouse models of TAAD may help to clarify the role of ADAMTS-5 in this disease.…”
Section: Proteoglycans and Proteoglycanases In Cardiovascular Physiology And Diseasementioning
confidence: 94%
“…Recombinant ADAMTS-5 reduced the LDLbinding ability of biglycan and released LDL particles from human aortic lesions [150], thus suggesting a role for this enzyme in regulating PG-mediated lipoprotein retention (figure 1a). ADAMTS-5 is expressed in both VSMCs [151,152] and macrophages [106], two cell types that also express versican [151,[153][154][155] and TIMP-3 [156][157][158], the major inhibitor of ADAMTS-4 and -5 [15]. Once a plaque is formed, its stability is associated with high expression levels of TIMP-3 [158,159] and versican [160].…”
Section: Adamts-5 Regulates Cardiovascular Proteoglycan Levelsmentioning
confidence: 99%
“…A protective role in atherosclerosis has been ascribed to ADAMTS5 as its expression was found depleted in atherosclerotic aortas, leading to the accumulation of proteoglycans such as versican and biglycan, which may favour lipid retention and macrophages. The risk of acute aortic dissection was independently associated with decreased plasma levels of ADAMTS5 (37).…”
Section: Adamtsmentioning
confidence: 96%
“…Among the three major proteoglycanases, ADAMTS5 protein has been found to be decreased in plasma [71] and increased in TAAD tissue compared to non-TAAD controls [66]; its mRNA levels were found to be decreased in two studies [6,70]. In a study which included 83 patients, an independent association was established between decreased plasma levels of ADAMTS5 and an increased risk of acute aortic dissection [71].…”
Section: Levels Of Adamts Proteases In Taadmentioning
confidence: 96%